Implementasi Animasi Motion Graphic Sebagai Media Pembelajaran Bahasa Arab di Madrasah Tsanawiyah Negeri (MTsN) 2 Palembang - Abdilah, M Arib; Ali Firdaus; Alan Novi Tompunu (Teknik Komputer Politeknik Negeri Sriwijaya, 2024)
The rapid development of technology, especially in learning, must be utilized. Therefore, to compensate for these technological developments, the use of motion graphic learning animation media will facilitate and assist in the teaching and learning process. With this background, the researcher will develop 2D motion graphic learning media for Grade 8 Arabic Language Learning. Researchers use the Luther method which has 6 stages, namely Concept, Design, Material Collecting, Assembly, Testing, and Distribution (Implementation). To determine the level of feasibility, the author used testing on 5 expert respondents and 30 respondents of 8th grade students of Madrasah Tsanawiyah Negeri (MTsN) 2 Palembang who studied Arabic language subjects with Likert scale calculation techniques. The results of this test get an assessment from the expert side on average calculated based on the Likert scale getting a score of 92% and is in the